2010
DOI: 10.1007/s00425-010-1186-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of coconut (Cocos nucifera L.) zygotic embryos does not induce morphological, cytological or molecular changes in recovered seedlings

Abstract: The present study aimed at exploring the fidelity of coconut (Cocos nucifera L.) plants recovered from cryopreservation. Zygotic embryos from various different cultivars were cryopreserved following four successive steps, namely: rapid dehydration, rapid freezing, rapid thawing and in vitro recovery followed by acclimatization. At the end of the acclimatization period, the seedlings were compared to counterparts of the same age, which were produced from non-cryopreserved embryos. Both series were submitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…0.8 % agar (to be kept in dark condition for 8 weeks), b Further development of shoot and roots on an embryo cultured plantlet. c Photoautotrophic system (CO 2 enrichment growth chamber) developed to improve seedling growth, d comparison between an acclimatized plantlet grown in a CO 2 enrichment environment and one covered by conventional plastic bag, e Plumule tissue emerging from a zygotic embryo and subsequently used as initial explant for callus induction, f-g different responses in callus induction media supplemented, respectively, with 200 lM and 600 lM 2,4-D, h Maturation of somatic embryos in a reduced 2,4-D medium, i aseptic isolation of zygotic embryos for cryopreservation, j rapid dehydration of sterilized embryos using fan-forced air apparatus, before being plunged into liquid nitrogen, k-l No significant differences in the morphology observed during the development and acclimatization of plantlets derived from cryopreserved embryos and normal embryos (these two photos are reprinted from Sisunandar et al 2010a, with permission) (P plumule, GP germ pore, NES non-embryogenic structures, GES globular embryogenic structures). Bar a, e, f-5 mm; g, h-1 mm; l-5 cm Planta protocol using CO 2 enrichment (1600 lmol mol -1 ) during the light phase was found to improve seedling health, growth, and the percentage of seedlings established (Samosir and Adkins 2014) (Fig.…”
Section: Haploid Culture 1979mentioning
confidence: 99%
See 2 more Smart Citations
“…0.8 % agar (to be kept in dark condition for 8 weeks), b Further development of shoot and roots on an embryo cultured plantlet. c Photoautotrophic system (CO 2 enrichment growth chamber) developed to improve seedling growth, d comparison between an acclimatized plantlet grown in a CO 2 enrichment environment and one covered by conventional plastic bag, e Plumule tissue emerging from a zygotic embryo and subsequently used as initial explant for callus induction, f-g different responses in callus induction media supplemented, respectively, with 200 lM and 600 lM 2,4-D, h Maturation of somatic embryos in a reduced 2,4-D medium, i aseptic isolation of zygotic embryos for cryopreservation, j rapid dehydration of sterilized embryos using fan-forced air apparatus, before being plunged into liquid nitrogen, k-l No significant differences in the morphology observed during the development and acclimatization of plantlets derived from cryopreserved embryos and normal embryos (these two photos are reprinted from Sisunandar et al 2010a, with permission) (P plumule, GP germ pore, NES non-embryogenic structures, GES globular embryogenic structures). Bar a, e, f-5 mm; g, h-1 mm; l-5 cm Planta protocol using CO 2 enrichment (1600 lmol mol -1 ) during the light phase was found to improve seedling health, growth, and the percentage of seedlings established (Samosir and Adkins 2014) (Fig.…”
Section: Haploid Culture 1979mentioning
confidence: 99%
“…Regarding production of homozygous inbred lines, Perera et al (2008b) have reported the production of doubled haploid plants via anther-derived embryogenesis. Furthermore, it is now possible to cryopreserve, and then recover coconut embryos for in long-term conservation programs, without inducing morphological, cytological or molecular changes in the regenerated plants (Sisunandar et al 2010a). Although genetic transformation in coconut has been attempted Andrade-Torres et al 2011), achievements have been quite limited to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sisunandar method [12] for embryo isolation from the nut and surface sterilization of the embryos was applied with minor modifications. After cracking the nuts, the zygotic embryos ( Figure 1(A)) with a small portion of endosperm were isolated from a specific region of the endosperm using a metal spoon.…”
Section: Plant Materialsmentioning
confidence: 99%
“…This medium then, may also be used for root induction in coconut embryo culture. The use of MS basal medium during the recovery process after incision and splitting showed that even though HEC medium is the most widely used medium for coconuts [4,[11][12][13][16][17], MS basal medium showed the best results during the recovery process of the incised embryos. Major differences in macronutrient composition between MS and HEC are the most plausible explanation for this result [18], as it is widely known that macronutrients such as nitrogen (in the form of NO 3 -and NH 4 + ) play an important role in both morphogenesis and growth.…”
Section: Embryo Incisionmentioning
confidence: 99%